Advocacy Groups Push Coding as a Core Curriculum. - SHUEH, JASON (Education Digest, 2014)
This article, reprinted and condensed from the June 25, 2014 issue of "Government Technology," profiles educational advocacy which promotes computer science programming as part of core curricula. Topics addressed include statistic citations regarding growth in computer programming jobs in the U.S., arguments asserting that curriculum development is necessary in the area of technology instruction, and the particular work of the Code.org advocacy campaign.